Processo de formação dos professores das séries iniciais do ensino fundamental: ouvindo professoras das quartas séries - Terra, Mara Teresinha Rodrigues (Universidade do Vale do Rio dos Sinos, 2010)
The current study aims to answer essentially the following questions, "How do performing teachers of 4th grades of Basic School putting themselves together as teachers?" And "What the involvement of that on their teaching practice?" On the searching of answers from those questions, you make the following aims, understanding the graduating course and be a teacher of those teachers, inquiring to analyse the specificiment or noto f proper knowledges of being a teacher from First Classes orespecially of Four_Grade; identifying the origem and the nature of knowledges acquired-built by those researched teachers and to identify the involvement (or not) those lnowledges/that formation of the teaching practices of those educators. The interlocutors of that research are (three) teachers that perform in the Four_Grade on State School, all of them with more than twenty years of tesching experience. One decided for listening teachers from Fourth Grades of basic School for considering this moment important on passing to the second stage from fifth to eighth grade of Basic School, where teachers have showm different qualities in respect to the other classes. The research is centralized in a qualitative approach and hás investigated to understand the graduating course of the researching teachers. It was possible to realize that reading of teaching its not a homogeneous proceeding, as each teacher develop a certainly way of being thinking the teaching profession, having as reference the proceeding of appropriation before being experiences different instructive contexts. Practice of teaching in the First grades and essentially in the Fourth Grades, demand of the skills and knwoledges link particulary to Integral Education with affective chains and the sensibility to helping the pupil through the change between the uniteaching and multiteaching; the continuity of the proceeding of the teaching of reading and instrumentaliation in order to the pupil deal with the universe of the worlds written, He needs to get into the habito f organization, with a strong encouragement to autonomy. These Knwoledges emphasized by the the interlocutors are built essentialy in their teaching practices, although they admit their academic backgroud as essential. The umderstanding about doing and teaching think involve to analyse factors, and events and their influences, evidencing the importance of studuing about formative courses as they make possible an approach with wishes, and anguishes, and feelings and worths, and knowledges and doings that are membres of the act/think feels teeaching, that were/are built/rebuilt in different formative times/spaces.
Keywords: Trajetórias formativas; Saberes docentes; Prática docente; Graduating courses; Teaching knowleges; Teaching pratices; ACCNPQ::Ciências Humanas::Educação